2019
DOI: 10.1021/acsanm.9b00574
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Stoichiometry and Electronic Structure of Cobalt Oxide in Thermally Treated Co-Doped ZnO Nanorods for Solar Cells

Abstract: The effects of annealing on the stoichiometry and electronic structure of Codoped ZnO nanorods (NRs), as prepared by chemical bath deposition (CBD), were investigated by photoemission spectroscopies (XPS and UPS) and X-ray diffraction (XRD). The Co 2p core level state of the as-grown Co-doped ZnO NRs is consistent with a Co 3 O 4 stoichiometry, independent of the Co concentration. Upon annealing of the as-grown material above 865 K, a Co 2p core level satellite state forms, which is consistent with the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
(150 reference statements)
1
11
0
Order By: Relevance
“…The tunneling process mediated by defect densities could cause shunting of the device and result in a lower reverse breakdown voltage. 39 This type of behavior can be seen in Fig. 9 with sizeable reverse leakage current and low photocurrent.…”
Section: I-v and Eqe Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…The tunneling process mediated by defect densities could cause shunting of the device and result in a lower reverse breakdown voltage. 39 This type of behavior can be seen in Fig. 9 with sizeable reverse leakage current and low photocurrent.…”
Section: I-v and Eqe Analysismentioning
confidence: 79%
“…For 10%, 15%, and 20% cobalt doping, we observe an additional spinel ZnCo 2 O 4 phase, which is a typically found spinel structure with Zn ++ ions in the tetrahedral sites and Co 3+ occupying the octahedral sites. In our previous studies, 39 we have discussed the detail Rietveld analysis of these nanomaterials and found that the percentage of the wurtzite ZnO phase in samples decreases and the secondary phase of ZnCo 2 O 4 increases with excessive cobalt concentration. However, for 10% cobalt doped samples, the existence of the ZnCo 2 O 4 secondary phase is low (<5%) in comparison to other higher doped samples.…”
Section: Structural Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…, Co diffuses easily into ZnO to form phases of Co-doped ZnO. 25–28 The Co pillars were observed to grow substantially larger than those in the Ni-doped ZnO, with an average height and width of 134.0 ± 2.4 nm and 31.5 ± 4.6 nm, respectively, in the 500 °C sample. The microstructure STEM cross-section image of the ZnO–Co composite grown at 700 °C is shown in Fig.…”
Section: Discussion/resultsmentioning
confidence: 98%
“…The nanocomposite was used in the electronic sensor . On the other hand, Co 3 O 4 was doped with manganese (Mn) to produce a unique mesoporous by a one‐stage hydrothermal process, which used an electrode of supercapacitors.…”
Section: Introductionmentioning
confidence: 99%